2013
DOI: 10.5935/0103-507x.20130040
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the EuroSCORE with the onset of postoperative acute kidney injury in cardiac surgery

Abstract: ObjectiveThe objective of this study was to assess the correlation between the European System for Cardiac Operative Risk Evaluation (EuroSCORE) score and the risk of developing acute kidney injury in cardiac surgery patients. MethodsThis retrospective study was conducted at a tertiary hospital on consecutive cardiac surgery patients (e.g., valvular, ischemic and congenital heart diseases) between October 2010 and July 2011. ResultsOne hundred patients were assessed. Among the 100 patients, six were excluded, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
3
0
2
Order By: Relevance
“…These outcomes can be predicted accurately using the standard EuroSCORE, which is very simple and easy to calculate [23]. de Moura et al [24] found that there is a statistically significant association between the values of EuroSCORE 1 and the risk of developing AKI in the postoperative period after cardiac surgery. Accordingly, D'Onofrio et al [21] found that patients developing CSA-AKI have more preoperative comorbidities as summarized by the higher EuroSCORE value.…”
Section: Discussionmentioning
confidence: 99%
“…These outcomes can be predicted accurately using the standard EuroSCORE, which is very simple and easy to calculate [23]. de Moura et al [24] found that there is a statistically significant association between the values of EuroSCORE 1 and the risk of developing AKI in the postoperative period after cardiac surgery. Accordingly, D'Onofrio et al [21] found that patients developing CSA-AKI have more preoperative comorbidities as summarized by the higher EuroSCORE value.…”
Section: Discussionmentioning
confidence: 99%
“…Several perioperative risk factors have been reported as predictors of AKI associated with cardiac surgery, including advanced age [11,12] , time interval of angiography and surgery [13] , blood transfusion [4,11,14] , preoperative elevated serum creatinine [15,16] , diabetes [17] , high-risk according to the EuroSCORE [18] , and use of nephrotoxic drugs. Use of cardiopulmonary bypass (CPB) has also been proposed to be a predictive factor for development of AKI after coronary artery bypass grafting (CABG) [19,20] .…”
Section: Introductionmentioning
confidence: 99%
“…O Quadro 2 apresenta as principais complicações identificadas no pós-operatório que acometeram os pacientes que realizaram as cirurgias cardíacas, com destaque para infecções respiratórias e pneumonia, acidente vascular encefálico, sangramentos, insuficiência renal e derrame pleural. A6 (22) 2014, Brasil 2060 Masculino: 1298 (63,00%) Coorte retrospectiva / 3C A7 (23) 2014, Brasil 4626 Masculino: 2933 (63,40%) Coorte retrospectiva / 3C A8 (24) 2014, Brasil 124 Masculino: 76 (61,29%) Transversal / 4B A9 (25) 2013, Brasil 2628 Masculino: 1836 (69,86%) Coorte bidirecional / 3C A10 (26) 2013, Brasil 94 Masculino: 54 (57,44%) Observacional / 3E A11 (27) 2013, Brasil 43 Masculino: 31 (72,09%) Coorte retrospectiva / 3C A12 (28) 2011, Brasil 211 Masculino: 126 (59,71%) Transversal / 4B A13 (29) 2010, Argentina 165 Masculino: 130 (78,78%) Observacional / 3E A14 (30) 2010, Brasil 85 Masculino: 52 (61,18%) Observacional / 3E A15 (31) 2010, Brasil 1038 Masculino: 706 (68,01%) Observacional / 3E A16 (32) 2009, EEUU 1163 Masculino: 826 (71,02%) Revisão sistemática de ensaios clín. random./ 1A A17 (33) 2000, Brasil 23 Masculino: 15 (65,22%) Observacional / 3E D1 (34) 2018, Brasil 118 Masculino: 77 (65,25%) Coorte retrospectiva / 3C D2 (35) 2012, Brasil 173 Masculino: 103 (59,54%) Observacional / 3E T1 (36) 2017, Brasil 725 Feminino: 393 (54,20%) Transversal / 4B T2 (37) 2017, Brasil 108 Feminino: 67 (62,04%) Ensaio clínico randomizado / 1C *n: amostra; **NE: nível de evidência.…”
Section: Resultsunclassified